Improving The Effective Methods of Developing Sports Tourism in the Regions - Oblokulov Ramazon Axtam o’g’li (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Sports tourism has emerged as a rapidly expanding segment of the global tourism industry, driving economic growth, infrastructure development, and cultural exchange. Specific Background: In Uzbekistan, the historic regions of Samarkand and Bukhara possess substantial potential for sports tourism, yet this potential remains underutilized due to limited facilities, inadequate marketing, and a shortage of qualified personnel. Knowledge Gap: Previous studies have rarely examined sports tourism development at a regional level in Central Asia, leaving limited empirical insights into strategies for integrating local infrastructure, management capacity, and international market positioning. Aims: This study aims to assess the current state of sports tourism in Samarkand and Bukhara, identify key challenges, and propose development strategies to enhance competitiveness. Results: Mixed-method analysis indicates significant growth in tourist interest and revenue, but reveals persistent constraints in modern sports infrastructure, digital marketing penetration, and professional skills among tourism operators. Novelty: The research provides one of the first strategic, evidence-based assessments linking sports tourism development with regional economic planning in these Uzbek regions. Implications: Strengthening infrastructure investment, targeted marketing, and specialized training programs can enhance regional competitiveness and position Samarkand and Bukhara as emerging destinations in the global sports tourism market.Highlight : Shows strong potential for expanding sports tourism in both regions. Key challenges include limited infrastructure and weak marketing efforts. Strategic investment and improved human resource capacity are required for development. Keywords : Sports Tourism, Samarkand, Bukhara, Infrastructure Development, Marketing Strategies